Brighter is darker: the Hamilton–Zuk hypothesis revisited in lizards. (27th June 2021) - Megía-Palma, Rodrigo; Barrientos, Rafael; Gallardo, Manuela; Martínez, Javier; Merino, Santiago
Abstract: Several studies of lizards have made an erroneous interpretation of negative relationships between spectral brightness and parasite load, and thus provided misleading support for the Hamilton–Zuk hypothesis (HZH). The HZH predicts that infected hosts will produce poorer sexual ornamentation than uninfected individuals as a result of energetic trade-offs between immune and signalling functions. To test whether there is a negative relationship between spectral brightness and pigment content in the skin of lizards, we used spectrophotometry to quantify the changes in spectral brightness of colour patches of two species after chemically manipulating the contents of orange, yellow and black pigments in skin samples. Carotenoids were identified using high-performance liquid chromatography. In addition, we compared the spectral brightness in the colour patches of live individuals with differential expression of nuptial coloration. Overall, the analyses demonstrated that the more pigmented the colour patch, the darker the spectrum. We provide a comprehensive interpretation of how variation in pigment content affects the spectral brightness of the colour patches of lizards. Furthermore, we review 18 studies of lizards presenting 24 intraspecific tests of the HZH and show that 14 (58%) of the tests do not support the hypothesis.